Variabilidade espacial da produtividade de frutos de pereiras e atributos químicos do solo. - Konopatzki, Marcia Regina Siqueira (2008)
In the last few years, the precision agriculture has turned itself to other crops besides cereals, which are already well-known studied. Among them, there is the precision horticulture. Pear is from mild weather and it is very appreciate by brazilian people, although its greatest consumed percentile is imported. Thus, this trial aimed at mapping spatial variability of chemical attributes from soil (P, K, Cu, Zn, Fe, Mn, Ca, Mg, pH, C and base saturation), of the plant (fruit length and diameter) as well as the pear trees yield in a commercial pear plants area. The experimental field had 146 pear plants, var. Pêra d água , distributed on a 1.24 ha area. Four harvest procedures were performed according to fruit maturation. In each harvest, the weight of all mature fruits per plant was computed, while the total yield was obtained by the sum of each crop. Hence, the soil attributes analyzed were: P, K, Ca, Mg, pH, CaCl2, C, Cu, Zn, Fe, Mn and base saturation, while the plants attributes were: length, diameter and yield. The pear yield had low correlation with soil attributes. Levels of spatial dependence were found to be very low (fruit length), low (P, fruit diameter), medium (Mg, pH, Cu, Zn, Fe), high (Ca, K, bases saturation and yield), and very high (Mn and C), according to the spatial variability index (SVI, %), as it is proposed in this study.